Newer approaches to malaria control - Damodaran, SE (Medknow Publications & Media Pvt Ltd, 2011)
Malaria is the third leading cause of death due to infectious diseases affecting around 243 million people, causing 863,000 deaths each year, and is a major public health problem. Most of the malarial deaths occur in children below 5 years and is a major contributor of under-five mortality. As a result of environmental and climatic changes, there is a change in vector population and distribution, leading to resurgence of malaria at numerous foci. Resistance to antimalarials is a major challenge to malaria control and there are new drug developments, new approaches to treatment strategies, combination therapy to overcome resistance and progress in vaccine development. Now, artemisinin-based combination therapy is the first-line therapy as the malarial parasite has developed resistance to other antimalarials. Reports of artemisinin resistance are appearing and identification of new drug targets gains utmost importance. As there is a shift from malaria control to malaria eradication, more research is focused on malaria vaccine development. A malaria vaccine, RTS,S, is in phase III of development and may become the first successful one. Due to resistance to insecticides and lack of environmental sanitation, the conventional methods of vector control are turning out to be futile. To overcome this, novel strategies like sterile insect technique and transgenic mosquitoes are pursued for effective vector control. As a result of the global organizations stepping up their efforts with continued research, eradication of malaria can turn out to be a reality.